2007
DOI: 10.1093/bja/aem218
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose ketamine affects immune responses in humans during the early postoperative period

Abstract: Addition of small doses of ketamine before induction of anaesthesia resulted in attenuation of secretion of the proinflammatory cytokines IL-6 and TNF-alpha, and in preservation of IL-2 production at its preoperative level. It is suggested that this anaesthetic may be of value in preventing immune function alterations in the early postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 36 publications
(24 reference statements)
6
84
1
4
Order By: Relevance
“…Several experimental and clinical studies have shown that, in addition to its anesthetic activity and analgesic effects, ketamine exerts anti-inflammatory properties by inhibiting the release of pro inflammatory cytokines, such as tumor necrosis factor-alpha and interleukin-6 [39][40][41][42][43]. Beilin et al [40] used small doses of ketamine before induction of anaesthesia in patients undergoing abdominal surgery and showed that there was attenuation of secretion of the proinflammatory cytokines IL-6 and TNF alpha, and in preservation of IL-2 production at its preoperative level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental and clinical studies have shown that, in addition to its anesthetic activity and analgesic effects, ketamine exerts anti-inflammatory properties by inhibiting the release of pro inflammatory cytokines, such as tumor necrosis factor-alpha and interleukin-6 [39][40][41][42][43]. Beilin et al [40] used small doses of ketamine before induction of anaesthesia in patients undergoing abdominal surgery and showed that there was attenuation of secretion of the proinflammatory cytokines IL-6 and TNF alpha, and in preservation of IL-2 production at its preoperative level.…”
Section: Discussionmentioning
confidence: 99%
“…Beilin et al [40] used small doses of ketamine before induction of anaesthesia in patients undergoing abdominal surgery and showed that there was attenuation of secretion of the proinflammatory cytokines IL-6 and TNF alpha, and in preservation of IL-2 production at its preoperative level.…”
Section: Discussionmentioning
confidence: 99%
“…Thiopentone, diazepam and ketamine have shown to negatively affect NK activity and lung tumor retention [59]. Thiopental and ketamine [94] also inhibit the LPSinduced release of IL-1, IL-6, TNF-α [95] and IL-8, and increase IL-10 [96][97]. In healthy volunteers, thiopentone and etomidate impair lymphocytes function [84].…”
Section: Intravenous Anestheticsmentioning
confidence: 99%
“…Preoperative use of small doses (0.15 mg/kg) of ketamine has been shown to suppress the inflammatory response and release of IL-6 and TNF-α, without altering IL-2 secretion [95]. Etomidate causes inhibition of T-lymphocyte function in vitro [101], but other studies have shown that etomidate does not affect NF-kappa B activation in human T-lymphocytes [102].…”
Section: Intravenous Anestheticsmentioning
confidence: 99%
“…A human study showed that low dose ketamine prior to induction of anesthesia prevented a significant suppression of lymphocyte proliferation. 19 Immunological effects appear to be dose-dependent. Animal studies have shown a significant increase in lung tumour retention with larger doses; 16 however, pre-treatment with a beta-blocker reduced this effect, suggesting involvement of ketamine's intrinsic adrenergic stimulating properties.…”
Section: Ketaminementioning
confidence: 99%